Minerals as advanced materials - Krivovichev, Sergey V.
This book comprises papers resulting from the 1st International workshop 'Minerals as Advanced Materials I'. It is intended as an exchange of ideas between mineralogists and material scientists. The aim is to identify minerals and mineral objects that have or potentially have unique physical, chemical and structural properties that are of interest from the viewpoint of applied mineralogy and material science.